2013
DOI: 10.1165/rcmb.2012-0347oc
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling in Neonatal and Adult Lung

Abstract: Sonic Hedgehog (Shh) signaling is essential during embryonic lung development, but its role in postnatal lung development and adult lung are not known. Using Gli1(nlacZ) reporter mice to identify cells with active Hh signaling, we found that Gli1(nlacZ)-positive mesenchymal cells are densely and diffusely present up to 2 weeks after birth and decline in number thereafter. In adult mice, Gli1(nlacZ)-positive cells are present around large airways and vessels and are sparse in alveolar septa. Hh-stimulated cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 52 publications
10
81
0
2
Order By: Relevance
“…Of these pathways, basal cell carcinoma signaling pathway represents constitutive activation of sonic hedgehog signaling. Molecules involved in sonic hedgehog signaling (e.g., sonic hedgehog homolog, patched, gliotactin) (39,40) and axonal guidance (e.g., Netrins, Slits, and Robo receptors, Semaphorins, Ephrins) (41)(42)(43)(44)(45) are well known to be involved in lung development, and our results suggest that DNA methylation may help regulate them.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Of these pathways, basal cell carcinoma signaling pathway represents constitutive activation of sonic hedgehog signaling. Molecules involved in sonic hedgehog signaling (e.g., sonic hedgehog homolog, patched, gliotactin) (39,40) and axonal guidance (e.g., Netrins, Slits, and Robo receptors, Semaphorins, Ephrins) (41)(42)(43)(44)(45) are well known to be involved in lung development, and our results suggest that DNA methylation may help regulate them.…”
Section: Discussionmentioning
confidence: 61%
“…The study group consisted of preterm infants with BPD (postmenstrual age, 28-42 wk; n = 6). For comparison, preterm stillbirths (24-to 26-wk gestation; n = 5) and term stillbirths (36)(37)(38)(39)(40) wk; n = 6) were used as control groups.…”
Section: Lung Tissue Samplesmentioning
confidence: 99%
“…Additionally, the exogenous expression of either Hh or VEGF has been shown to additively contribute to TGF-β-driven fibrotic disease progression in animal models (33)(34)(35)). Our results demonstrate that ITA antagonizes both Hh and VEGF signaling pathways in HSCs and that chemical inhibition of both signaling pathways together is sufficient to recapitulate ITA's inhibitory effect on MFB formation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed a reactivation of the Shh pathway in bleomycin-induced fibrotic lungs and in human IPF lungs (109)(110)(111). This might lead to aberrant epithelial-fibroblast interaction and induction of fibroblast cell proliferation.…”
Section: Mirnas In Embryonic Lung Mesenchyme Mir-326 As Part Of the Smentioning
confidence: 99%